Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2478/v10181-011-0057-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of canine parvovirus CPV-2 strains and its variants isolated in Poland

Abstract: Canine parvovirus disease appeared in the world and in Europe during the second half of the 1970s. Over the course of 40 years the original CPV-2 strains mutated and variants 2a, 2b and 2c appeared. Their appearance is connected with specific amino acid changes, mainly in the capsid protein VP2. Strains isolated by the authors were adapted for in vitro cell culture. Phylogenetic analysis revealed differences between strains isolated in Poland in 1982-1985 and in 1995-2009. Strains from the 1980s were shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…Analogous to other geographical areas, the original type CPV-2 was shown not to circulate in dogs, whereas type 2a was the most frequently detected variant, which was in agreement with reports in other eastern European countries. 7,8,18,20 However, CPV-2c was also detected in a high proportion of CPV PCR-positive fecal samples not previously observed in eastern Europe. As for CCoV infection, a larger number of CCoV-IIa subtypes were detected compared with CCoV-IIb (CCoV-TGEV recombinant strains).…”
Section: Research-article2014mentioning
confidence: 87%
See 1 more Smart Citation
“…Analogous to other geographical areas, the original type CPV-2 was shown not to circulate in dogs, whereas type 2a was the most frequently detected variant, which was in agreement with reports in other eastern European countries. 7,8,18,20 However, CPV-2c was also detected in a high proportion of CPV PCR-positive fecal samples not previously observed in eastern Europe. As for CCoV infection, a larger number of CCoV-IIa subtypes were detected compared with CCoV-IIb (CCoV-TGEV recombinant strains).…”
Section: Research-article2014mentioning
confidence: 87%
“…2,3 Canine coronavirus type II is divided into 2 subtypes, IIa (classical strains) and IIb, with CCoV-IIb emerging as a result of a putative recombination between CCoV-IIa and TGEV. 13 Several studies have assessed the CPV and/or CCoV type distribution in different European countries, [6][7][8]13,18,20,21 but, to date, there is no epidemiological data about the circulation of these enteric pathogens in Albania. Thus, the main purpose of the present study was to determine the frequency of CPV-2 and CCoV infections in dogs with diarrhea in Albania and to characterize the viral types that circulate in this country.…”
Section: 9mentioning
confidence: 99%
“…Battilani et al (2006) confirmed a high degree of variation in the sequence encoding the VP2 coat protein in parvoviruses infecting dogs and cats. Even minor changes in the nucleotide and amino acid sequence can have a significant effect on biological characteristics and pathogenicity (Majer-Dziedzic et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Changes were also observed in single cases in each group, including S393T, occurring in one of the wild animals, and L418H, D433H and D474E in representatives of the farmed animals. Single changes in the amino acid sequence may be of key importance for pathogenicity; it is theorized that nonsynonymous changes in the gene encoding VP2 in FPLV led to the emergence of CPV-2 [20]. Substitutions in this protein led to the separation of variants a, b and c, which supplanted the original strain; a change in just one amino acid enables differentiation of the pathogen into variants a and b [21].…”
Section: Discussionmentioning
confidence: 99%